Assessment of Facilities Management Performance in Selected Real Estate Business: Basis for Crafting a Policy Framework - Chrystina Lynn J. Lopez; Jay A. Sario; Ericson Z. Matias (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Facilities Management (FM) role becomes more significant in the day-to-day operations of most of organizations. The FM team ensures that operations of organizations will run smoothly without downtime, provide safe working environment, comply with regulators, and provide one-stop-shop service for employees that can benefit the organization in retaining and attracting top talents. This research aims to assess the performance of FM before the pandemic, and the start of the new normal and compare the operations on these timelines to identify the inefficiencies and opportunities for improvement that can lead to an effective, efficient, and consistent quality performance. The researcher includes the assessment of gaps, management capabilities, technologies, factors influencing performance and productivity, and ways of adapting to the changing external business landscape. To interpret the collected data, frequency and percentage, mean and standard deviation, Pearson-r correlation were used in quantitative data, and thematic analysis for the qualitative responses. The data gathered from the FM team supporting different clients and as senior leaders, signifies that there is no significant difference in operations and technology to support clients. However, minor improvements and recommendations by senior leaders can be considered and can contribute to effective and efficient operations.